2012
DOI: 10.1680/macr.11.00076
|View full text |Cite
|
Sign up to set email alerts
|

Using Hopkinson pressure bar to perform dynamic tensile tests on SFRC at medium strain rates

Abstract: The dynamic tensile strength of steel fibre reinforced concrete is experimentally investigated. Cylindrical specimens are first fabricated with three different fibre volume fractions of 0, 0 . 75% and 1 . 5%. These specimens are then tested by using the Hopkinson pressure bar technique. Their dynamic tensile strengths are measured under medium strain rate impact. In these tests, the stress histories are recorded by way of the strain gauges symmetrically mounted on the specimen and the post-test fracture modes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…It is assumed that the value of E c is the same for both tensile and compressive regimes and can be estimated by Eq. (21). It is considered that the ultimate compressive strain has a value of 0.0035.…”
Section: Constitutive Lawsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is assumed that the value of E c is the same for both tensile and compressive regimes and can be estimated by Eq. (21). It is considered that the ultimate compressive strain has a value of 0.0035.…”
Section: Constitutive Lawsmentioning
confidence: 99%
“…DIF of a certain material property is the ratio of its dynamic to quasi-static values. Studies conducted on the dynamic behavior of SFRC have demonstrated that higher loading strain rates lead to an increase in both the tensile strength and mode-I fracture energy, [13][14][15][16][17][18][19][20][21][22]. Consequently, both tensile and flexural behavior of concrete are rate dependent parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies used cementitious materials such as mortar and concrete. However, very limited research has been carried out using FRC composites, see (11,12). It has been reported by many researchers that the addition of fibers into the brittle matrix can significantly increase the tensile strength, ductility, toughness, and post-cracking behavior (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…The split Hopkinson pressure bar (SHPB) system, which was invented by Kolsky (1953), is an ideal and reliable loading technique to measure the dynamic properties of rock under a middlehigh strain rate. Over the past decades, the SHPB has been widely used in the study of material dynamic properties, and many research results have been acquired (Zhao and Li 2000;Wang, Zhou, and Wang 2012;Wang, Li, and Xie 2009). With the dynamic force balance achieved by the pulse shaping technique, it was proved that in a dynamic Brazilian disc (or splitting) test, the time-varying dynamic forces on both ends of the sample were almost identical .…”
Section: Introductionmentioning
confidence: 99%